2001
DOI: 10.1074/jbc.m009690200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Multispecificity of Arabidopsis Vacuolar Multidrug Resistance-associated Protein-type ATP-binding Cassette Transporter, AtMRP2

Abstract: Recent investigations have established thatArabidopsis thaliana contains a family of genes encoding ATPbinding cassette transporters belonging to the multidrug resistance-associated protein (MRP) family. So named because of the phenotypes conferred by their animal prototypes, many MRPs are MgATP-energized pumps active in the transport of glutathione (GS) conjugates and other bulky amphipathic anions across membranes. Here we show that Arabidopsis MRP2 (At-MRP2) localizes to the vacuolar membrane fraction from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 43 publications
7
117
1
Order By: Relevance
“…The Arabidopsis ABC subfamily C (ABCC) transporters AtABCC1 and AtABCC2 were previously demonstrated to localize to the vacuolar membrane (Liu et al, 2001;Geisler et al, 2004) and have been shown to transport organic anion conjugates (Lu et al, 1998;Liu et al, 2001). AtABCC14 is also localized to the tonoplast, as shown by several proteomic analyses (Carter et al, 2004;Shimaoka et al, 2004;Jaquinod et al, 2007).…”
Section: Kinetics Of Vacuolar Aba-ge Importmentioning
confidence: 96%
See 2 more Smart Citations
“…The Arabidopsis ABC subfamily C (ABCC) transporters AtABCC1 and AtABCC2 were previously demonstrated to localize to the vacuolar membrane (Liu et al, 2001;Geisler et al, 2004) and have been shown to transport organic anion conjugates (Lu et al, 1998;Liu et al, 2001). AtABCC14 is also localized to the tonoplast, as shown by several proteomic analyses (Carter et al, 2004;Shimaoka et al, 2004;Jaquinod et al, 2007).…”
Section: Kinetics Of Vacuolar Aba-ge Importmentioning
confidence: 96%
“…Several MATE and ABCC-type proteins implicated in vacuolar conjugate transport have been shown to be multispecific (i.e. they transport structurally unrelated compounds, whereby the affinities toward the individual substrates vary considerably; Liu et al, 2001;Martinoia et al, 2012). The low affinity of the ABA-GE transport further suggests that multispecific transporters involved in the vacuolar sequestration of different metabolites also mediate the uptake of ABA-GE.…”
Section: Atabcc1 and Atabcc2 Transcript Levels And Knockout Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…In A. thaliana, 8 of the 15 MRPs are found in homologous pairs that can have >85% sequence identity Kolukisaoglu et al, 2002). Interestingly, the highly homologous pair AtMRP1 and AtMRP2 shows both significant overlap of, and fundamental differences in, their in vitro substrate preferences Liu et al, 2001). Therefore, both functional redundancy and unique biological roles likely exist for closely related MRPs.…”
Section: Introductionmentioning
confidence: 99%
“…Substrates are not limited to glutathionated compounds but include a range of heterocyclic organic anions and heavy metals . Such compounds may or may not be conjugated to sugars or amino acids and can be transported alone or in conjunction with free GSH (Liu et al, 2001). In humans, MRP substrates include anticancer drugs and other xenobiotics, including plant flavonoids, and endogenous molecules, such as bile salts and leukotrienes (Borst et al, 1999).…”
Section: Introductionmentioning
confidence: 99%